Fungal bioremediation of the creosote-contaminated soil: influence of Pleurotus ostreatus and Irpex lacteus on polycyclic aromatic hydrocarbons removal and soil microbial community composition in the laboratory-scale study - Byss, Marius; Elhottová, Dana; Tříska, Jan; Baldrian, Petr (Chemosphere, 2008)
The aim of this study was to determine the efficacy of selected basidiomycetes in the removing of polycyclic aromatic hydrocarbons (PAH) from the creosote-contaminated soil. Fungi Pleurotus ostreatus and Irpex lacteus were supplemented with creosote-contaminated (50-200 mg kg(-1) PAH) soil originating from a wood-preserving plant and incubated at 15 °C for 120 d. Either fungus degraded PAH with 4-6 aromatic rings more efficiently than the microbial community present initially in the soil. PAH removal was higher in P. ostreatus treatments (55-67%) than in I. lacteus treatments (27-36%) in general. P. ostreatus (respectively, I. lacteus) removed 86-96% (47-59%) of 2-rings PAH, 63-72% (33-45%) of 3-rings PAH, 32-49% (9-14%) of 4-rings PAH and 31-38% (11-13%) of 5-6-rings PAH. MIS (Microbial Identification System) Sherlock analysis of the bacterial community determined the presence of dominant Gram-negative bacteria (G-) Pseudomonas in the inoculated soil before the application of fungi. Complex soil microbial community was characterized by phospholipid fatty acids analysis followed by GC-MS/MS. Either fungus induced the decrease of bacterial biomass (G- bacteria in particular), but the soil microbial community was influenced by P. ostreatus in a different way than by I. lacteus. The bacterial community was stressed more by the presence of I. lacteus than P. ostreatus (as proved by the ratio of the fungal/bacterial markers and by the ratio of trans/cis mono-unsaturated fatty acids). Moreover, P. ostreatus stimulated the growth of Gram-positive bacteria (G+), especially actinobacteria and these results indicate the potential of the positive synergistic interaction of this fungus and actinobacteria in creosote biodegradation.
Keywords: Biodegradation, Environmental; biodegradace; Soil Pollutants; Soil Microbiology; kreosot; Polyporales; látky znečišťující půdu; Biomass; Creosote; půdní mikrobiologie; polycyklické aromatické uhlovodíky; mikrobiální společenstva; Bacteria; Polycyclic Aromatic Hydrocarbons; Pleurotus; biomasa; Microbial Consortia